TOWARDS A NEW UNIVERSITY - Cevallos A., Juan (2003)
This article deals with the New University and the main conceptions it ought to comply with, through ideas development and shaping, based on systemic thought and following a concurrence of methodologies of the Checkland, Forrester and Senge's Soft Systems.